Detection of anti-Leptospira inhibitory antibodies in horses after vaccination. (September 2017) - Correia, Lucas; Martins, Gabriel; Lilenbaum, Walter
Abstract: Leptospirosis is a relevant zoonosis that affects the reproductive performance of livestock, impairing the economy. Few studies have demonstrated the effects of vaccination against leptospirosis on naturally exposed horses. This study aimed to detect anti- Leptospira inhibitory antibodies in horses after vaccination. A total of 54 mares were studied using Growth Inhibition Test (GIT) in three moments. The present results demonstrate the usefulness of GIT for confirming inhibitory effects of specific antibody production. Results have also demonstrated that vaccination positively influenced on the presence of inhibitory antibodies in horses. Highlights: Usefulness of GIT for confirming inhibitory effects of specific antibody production. Vaccination positively influenced on the presence of inhibitory antibodies in horses. The main increase on inhibitory antibodies occurred between D30pv and D90pv, after booster dose performed on D40pv.